2022
DOI: 10.1021/acsanm.2c04276
|View full text |Cite
|
Sign up to set email alerts
|

ZIF-8-Supported AgInS2 Quantum Dots for Photocatalytic H2 Production by Precise Location Sulfurization

Abstract: Although quantum dots (QDs) have unique properties that are different from conventional semiconductors, their photocatalytic activity and stability are far from expectations, and the preparation of semiconductor composites has become an important means to improve their photocatalytic hydrogen production performance. A convenient and safe coordinationassisted self-assembly method was used to encapsulate QDs into metal−organic frameworks and further formed AgInS 2 @ZIF-8/ ZnS nanostructures by converting part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Meanwhile, the tail is very long in the long wave direction, which corresponds to the absorption spectrum characteristics of multiple QDs [45] . As shown in Figure 5 (b) and Figure S4, the PL intensity of AIS/ZIF composite is reduced compared with the pristine AIS QDs, indicating the lower electron‐hole recombination rate [46] . In addition, Since AIS QDs were embedded in the ZIF‐70 matrix, the fluorescence emission of AIS/ZIF composite was blocked by the framework of ZIF‐70, [26] which also leads to the decrease of PL intensity.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Meanwhile, the tail is very long in the long wave direction, which corresponds to the absorption spectrum characteristics of multiple QDs [45] . As shown in Figure 5 (b) and Figure S4, the PL intensity of AIS/ZIF composite is reduced compared with the pristine AIS QDs, indicating the lower electron‐hole recombination rate [46] . In addition, Since AIS QDs were embedded in the ZIF‐70 matrix, the fluorescence emission of AIS/ZIF composite was blocked by the framework of ZIF‐70, [26] which also leads to the decrease of PL intensity.…”
Section: Resultsmentioning
confidence: 89%
“…[45] As shown in Figure 5 (b) and Figure S4, the PL intensity of AIS/ZIF composite is reduced compared with the pristine AIS QDs, indicating the lower electron-hole recombina- Chemistry-A European Journal tion rate. [46] In addition, Since AIS QDs were embedded in the ZIF-70 matrix, the fluorescence emission of AIS/ZIF composite was blocked by the framework of ZIF-70, [26] which also leads to the decrease of PL intensity. Meanwhile, the peak position shows a red-shift gradually with the decrease of ZIF-70 addition amount, which is attributed to the fact that the aggregation of QDs causes the increase of quantum sizes.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the cooperation of ZIFs with bimetallic sulphide also demonstrated effectiveness in improving photocatalytic hydrogen production. Loading AgInS 2 on the ZIF-8 surface allowed the partial transition of ZIF-8 into ZnS and the formation of AgInS 2 @ZIF-8/ZnS nanostructures, reported by Yu et al 132 Photoelectrochemical measurements confirmed a significant increase in the migration and separation of photogenerated carriers in the presence of AgInS 2 quantum dots (QD). The composite reached an optimal HER rate of 9.79 mmol g −1 h −1 .…”
Section: Water Splittingmentioning
confidence: 74%
“…With increasing global energy consumption, efforts to harness renewable energy sources continue to gain traction. , Of particular interest are ternary semiconductor materials that can efficiently capture, convert, and store sunlight and are being investigated. The conventional approach in photocatalysis involves photoirradiation of semiconductor suspensions or slurries to induce the desired chemical transformation.…”
Section: Introductionmentioning
confidence: 99%